1999
DOI: 10.1046/j.1365-313x.1999.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

5′ to 3′ exoribonucleolytic activity is a normal component of chloroplast mRNA decay pathways

Abstract: SummaryMolecular genetic studies have shown that determinants of chloroplast mRNA stability lie in both the 5¢ and 3¢ untranslated regions. While it is wellknown that chloroplast mRNAs are unstable in the absence of certain nucleus-encoded factors, little is known of the decay mechanisms for chloroplast mRNA in wild-type cells. Here we used a poly(G) 18 sequence, which impedes both 5¢®3¢ and 3¢®5¢ exoribonucleolytic RNA decay in vivo, to study the degradation pathway of petD mRNA in wild-type and mcd1 mutant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 59 publications
4
52
0
Order By: Relevance
“…It has also been reported that a 5Ј-to 3Ј-exoribonucleolytic activity is involved in RNA degradation pathways in Chlamydomonas chloroplasts (21). Here, we present two lines of evidence strongly in favor of the involvement of a 3Ј-to 5Ј-exonuclease activity in the degradation of plant mitochondrial polyadenylated mRNAs.…”
Section: Discussionsupporting
confidence: 58%
“…It has also been reported that a 5Ј-to 3Ј-exoribonucleolytic activity is involved in RNA degradation pathways in Chlamydomonas chloroplasts (21). Here, we present two lines of evidence strongly in favor of the involvement of a 3Ј-to 5Ј-exonuclease activity in the degradation of plant mitochondrial polyadenylated mRNAs.…”
Section: Discussionsupporting
confidence: 58%
“…Five additional strains were created that have insertions at the ϩ25 position relative to the mature uidA mRNA 5Ј end. We have previously shown that deletions up to ϩ25 do not affect transcription rates (19) and that small mutations or a polyguanosine insertion within the ϩ1-25 region do not decrease petD RNA levels (21,28). In addition, the sequences around this position are not important for petD mRNA 5Ј end maturation (28), although any insertion into this site translationally inactivates the message for unknown reasons.…”
Section: Fig 2 Sequence Requirements For Ecs-originated Downstream mentioning
confidence: 99%
“…RNA was isolated from 10 ml of cells as previously described (21). For RNA filter hybridizations, 10 g of total RNA was fractionated in 1.2% agarose, 6% formaldehyde gels, transferred to Hybond-N (Amersham Biosciences, Inc.), and cross-linked by UV irradiation.…”
Section: Rna Isolation Filter Hybridizations and Primer Extensionmentioning
confidence: 99%
“…Thus, primary triphosphorylated transcripts are thought to be largely impervious to RNase J exonucleolytic attack. Chloroplasts are known to have a net 59 / 39 RNA degradation pathway (Drager et al 1999;Hicks et al 2002), and RNase J has also been proposed to catalyze 59 end trimming of monocistronic RNAs and polycistronic transcript derivatives, being stalled by gene-specific RNA binding proteins (see Fig. 2 in Barkan 2011).…”
Section: Introductionmentioning
confidence: 99%